Problems in the Application of the Principle of Freedom of Contract in Commercial Property Lease Agreements - Hayati, Winta (Fox Justi : Jurnal Ilmu Hukum, 2025)
The development of business activities in Indonesia has driven high demand for commercial property, making lease agreements a frequently used legal instrument by business actors. This research aims to examine the problems of implementing the freedom of contract principle in commercial property lease agreements in Indonesia. The research method used is normative legal research with statutory and conceptual approaches, utilizing secondary data consisting of primary, secondary, and tertiary legal materials analyzed qualitatively. The research results show that the implementation of the freedom of contract principle faces problems in the form of unequal bargaining positions between property owners and tenants due to the widespread use of standard agreements drafted unilaterally. Many clauses are found to burden tenants such as imposing all repair costs, unilateral rent increases, and termination of agreements at any time by owners. Legal protection efforts can be made through the application of the good faith principle and proportionality principle as well as the provisions of Article 18 of the Consumer Protection Law which prohibits standard clauses that transfer business actor responsibilities. Therefore, the freedom of contract principle must be limited to achieve fairness for all parties.